What active labour market programmes work for immigrants in Europe? A meta-analysis of the evaluation literature - Sebastian Butschek; Thomas Walter (IZA Journal of Migration, 2014)
A growing body of programme evaluation literature recognises immigrants as a disadvantaged group in European labour markets and investigates the employment effects of Active Labour Market Programmes (ALMPs) on this subgroup. So far, however, there is no systematic review establishing which ALMPs are effective for immigrants. Using a meta-analysis, we condense 93 estimates from 33 empirical studies of the effectiveness of four types of ALMPs employed across Europe to combat immigrant unemployment: training, job search assistance, wage subsidies and subsidised public sector employment. We find that only wage subsidies can be confidently recommended to European policy-makers.
Keywords: J15; J61; J68; I38; 330; Immigrants; Unemployment; Labour market integration; ALMP; Evaluation; Meta-analysis